Global research trends in immunotherapy for head and neck neoplasms: A scientometric study. Issue 4 (April 2023) - Jiang, Zhou; Wu, Chenzhou; Zhao, Yiming; Zhan, Qi; Wang, Kunyu; Li, Yi
Abstract: In recent decades, the traditional treatment of head and neck neoplasms has reached a bottleneck with limited improvement in overall survival. Nevertheless, the emerging field of immunotherapy has shown promise. Literature on research into immunotherapy for head and neck neoplasms was retrieved from WoSCC. Citespace was used as a scientometric analysis tool for text mining and visualization of the scientific literature. This analysis included 1915 documents. Recently, the annual number of publications and citations has been growing rapidly. 'Oncology' was the most popular research area. The most dominant institution and country were the University of Pittsburgh and the USA. Ferris RL was not only the most prolific but also the most cited author, demonstrating a strong influence and reputation. Of the ten core journals identified in this field, Cancer Research ranked first. 'Regulatory T cell', 'PD-1' and 'biomarker' were regarded as current hotspots, while 'recurrent' and 'nivolumab' were considered as trending keywords. The most cited reference was Ferris RL (2016). Notably, the front trends and future directions in the field may lie in the clinical practice of combination therapy of immunotherapy plus other therapies, the mechanism of impaired immune surveillance, and the improvement in resistance to immunotherapeutic agents. It is firmly believed that the present scientometric analysis has provided both a macroscopic and microscopic overview of research into immunotherapy for head and neck neoplasms, which will assist researchers and oncologists to better understand this discipline and thus promote further development and policies in this field. Highlights: The research could be divided into three periods: initial period, development period and boom period. Ferris RL was not only the most productive but also the most cited author. "Core journals" were identified in this field according to Bradford's law， and  Cancer Research  ranked first. Front trends may lie in three directions: combination therapy, impaired immune surveillance and the resistance to ICIs.